Islamic Economic Thought Abu Yusuf, Al-Ghazali, Asy-Syatibi (Comparative Study of Relations, Comparison and Relevance with Modern Islamic Economics) - Munawir*, Al; Azwar, Muhammad; Khaliza, Sukma; Yusuf, Muhammad Yasir (Riwayat: Educational Journal of History and Humanities, 2023)
Abu Yusuf, Al-Ghazali and Asy-Syathibi are muslim scientists who have put a lot of their thoughts into the economic field such as in the field of public finance, the role of the government in the movement of the country's economy and the theory of maqashid sharia in order to realize the welfare of the ummah. In the economic field, the three figures direct their thoughts in making policies that can provide solutions, support, encourage and create prosperity for the state and its citizens. This study aims to explain the relationship of thought between figures, relationships and relevance in the Indonesian economy at this time. This research belongs to the type of qualitative research and data collection methods through library research (library research). The results of this study indicate that the thoughts of previous economic leaders are still very much in line with today's modern economic realities, including in the aspects of public finance, the role of the state in the economy and the implementation of maqashid syariah.